STUDENTS' INDEPENDENT WORK IN HIGHER EDUCATION: ESSENCE AND METHODOLOGY (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article substantiates the significance of students' independent work in higher education. The educational process at universities imposes specific and higher demands on independent learning, driven by the necessity for students to acquire complex general cultural and professional competencies. One of the most critical tasks of higher education is to develop students' ability to self-organize, self-actualize, and establish themselves as active participants in the educational process. The article examines the objectives of independent student work, emphasizing creative forms of learning. It argues that the effectiveness of independent work largely depends on methodological approaches, with the most important being the subject-personal and activity-creative approaches.